Shear lag including axial balance of box beams by finite segment model. (February 2022) - He, Xiaoyang; Xiang, Yiqiang; Qiu, Xin; Chen, Zhengyang
Abstract: A finite segment element including axial balance is formulated to describe shear lag in thin-walled box beams having constant or variable cross sections made from steel or other materials. The axial balance neglected in the conventional finite segment element model (CFSM) is enforced by adding the nodal longitudinal displacements, while shear lag and shear deformation are incorporated using the nodal shear lag functions and rotations, respectively. The homogeneous solutions deduced by the analytical method are utilized for constructing the element shape functions. By invoking the minimum potential energy theorem, the stiffness matrix and the equivalent nodal force vector are then derived for the element. The precision of the proposed finite segment model (PFSM) is verified against the results yielded from the solid finite element model (SFEM), the finite strip model (FSTM), and the experiments. A continuous box beam having varying cross sections is chosen for comparing the neutral axis depth to the centroidal axis depth. Subsequently, the influence of the axial balance on the mechanical behavior is evaluated. Moreover, the effects of three major geometric parameters are discussed for stress analysis. The results reveal that the proposed finite segment model is capable of reproducing the mechanical behavior of box beams having constant or varying cross sections, and that the stress analysis concerning the continuous box beam with variable cross sections is substantially affected by the axial balance condition. Graphical abstract: Unlabelled Image Highlights: A segment element including axial balance is formulated to model shear lag in thin-walled box girders. Axial balance is enforced by adding the nodal longitudinal displacements. The impact of axial balance is quantified for box girders having variable cross sections.